Effects of specimen geometry and size on mode I and mixed mode fracture behavior of high strength fiber reinforced concrete - Mohammed Mutnbak; Abdulrahman Abbadi; Saeed Mousa; Amr A. Abd-Elhady; Hossam El-Din M. Sallam; Ramy M. Reda (Scientific Reports)
Abstract High-strength concrete (HSC) and polypropylene fiber-reinforced concrete (PPFRC) as quasi-brittle materials generally experience fracture failure either in mode I (tensile mode) or in mixed mode I and II (tensile and shear), which are the most common forms of damage in structural engineering. This study investigates the fracture behavior of HSC and PPFRC under Mode I and mixed-mode loading conditions. Both numerical simulation and experimental investigation were conducted to analyze the fracture toughness and crack paths of Semi-Circular Bend (SCB) specimens. The Extended Finite Element Method (X-FEM) was employed in the numerical simulations to model crack propagation under different modes of mixtures. The experimental results showed that the crack followed a curvilinear trajectory under mixed mode loading while propagating parallel to the applied load under pure Mode I loading. The numerical simulations using X-FEM demonstrated good agreement with the experimental results.